Heuristic solutions related to challenges of optical burst switching paradigm - Garg,Amit Kumar (2011)
Several optical network switching paradigms have been under intensive research to support rapidly increasing bandwidth requirements. Of all these paradigms, optical burst switching (OBS) is a promising switching paradigm for the next-generation Internet infrastructure. Despite the significant contributions of OBS to high speed networks such as dynamic connection setup and strong separation between data and control plane, there are several issues that are to be resolved because the present OBS research studies have many differences and thus need further study. In this paper, some of author's own past researches have been summarized to overcome few issues of OBS; related to network architectures, contention, burst assembly, congestion, complex scheduling schemes, quality of service (QoS), burst dropping , routing etc.